Estudio doctrinario y jurídico del silencio administrativo y de sus efectos dentro del procedimiento administrativo en el Ecuador - García Herrera, Gabriela Solange (2017)
Consequently my subject area i located in the review of some aspects related with the administrative law, that being part of public law and of relevance and significance within the human relations, constitutes an ideal space to identify legal problems that affect and general negative impacts within the public administration. Precisely one of the critical knots in the actions between public administration and the administered that has for decades been the subject of questions and broad debate is the institution of the administrative silence, which is closely related to the right of petition recognized in the Constitution of the Republic. The administrative silence constitutes an important object of study by their importance in relations between the State and individuals, it is a central institution in administrative law that has lacked relevance properly and its effective implementation has been limited to legal and procedural constraints that has restricted its application and development as a guarantee of the administered in front of the public administration. It is important to make reference to the legal framework that regulates this institution and which in this case is the Law of Modernization of the State, the same as in its Art. 28 to regulate matters relating to administrative silence and taking as an antecedent to the right of petition, set the following: "Art. 28.- Right of petition.- All claims, application or request to a public authority must be resolved within a period of not more than fifteen days from the date of its submission, except that a legal rule expressly point to another. In any administrative organ shall be suspended the processing or refuse the issuance of a decision on the requests or claims presented by the administered. In all cases expired the respective term is understood by the administrative silence, that the application or request has been approved or that the claim has been resolved in favor of the claimant. To this effect, the competent official of the institution of the State shall have the obligation to deliver, at the request of the interested party, under penalty of dismissal, a certificate indicating the expiration of the term mentioned above, which will serve as a public instrument to demonstrate that the claim, request or order has been favorably resolved by administrative silence, in order to allow the holder to exercise the rights that correspond." From this provision, we can identify the problems that will be discussed extensively in this study by constitute a legal problem within the public administration.